FAKTOR-FAKTOR PENYEBAB KETERLAMBATAN PENGKLAIMAN BPJS RAWAT INAP DI RUMAH SAKIT UMUM IMELDA PEKERJA INDONESIA (RSU IPI) MEDAN TAHUN 2020 - Erlindai Purba (Akademi Perekam dan Informasi Kesehatan Imelda, 2020)
The Social Security Organizing Agency (BPJS) is an institution formed to organize a Social Security Program in Indonesia based on Law Number 40 of 2004 and Law Number 24 of 2011. Indonesian General Imelda Worker Hospital is a private hospital in the city of Medan who have collaborated with BPJS Based on the initial survey of researchers on 30 medical records documents 13 files (43%) are in accordance with claim requirements and 17 files (56%) are incomplete. Data collection in this study is a questionnaire method. This research was conducted using quantitative research methods with cross sectional approach. The population used in this study were all medical record officers in the medical record unit in the IPI General Hospital Medan as many as 31 officers. Based on the results of a statistical test research conducted using the Chi Square (X2) computer test application with a significance of 95% (p <0.05) it can be concluded that the Hospital conducts an evaluation for medical records officers so that the performance of officers is as expected. Increase evaluation for the completeness of medical record documents used in BPJS claims.